Endocrine disruptors and neonatal anthropometry, NICHD Fetal Growth Studies - Singletons. (October 2018) - Buck Louis, Germaine M.; Zhai, Shuyan; Smarr, Melissa M.; Grewal, Jagteshwar; Zhang, Cuilin; Grantz, Katherine L.; Hinkle, Stefanie N.; Sundaram, Rajeshwari; Lee, Sunmi; Honda, Masato; Oh, JungKeun; Kannan, Kurunthachalam
Abstract: Background: Intrauterine exposure to endocrine disrupting chemicals (EDCs) has been equivocally associated with birth weight, length and head circumference with limited attention to anthropometric endpoints such as umbilical circumference and limb lengths. Objective: To explore 76 prenatal maternal plasma EDC concentrations in a healthy obstetric cohort and 7 neonatal anthropometric endpoints by maternal race/ethnicity. Methods: The study cohort comprised 2106 (564 White, 549 Black, 590 Hispanic, 403 Asian) healthy pregnant women recruited from 12 U.S. clinical sites between 2009 and 2012 who were followed through delivery. Neonates underwent standardized anthropometric assessment (weight, length, head and umbilical circumference, and mid- upper arm and thigh length). Plasma EDC concentrations were quantified using high resolution gas chromatography-high resolution mass spectrometry and liquid chromatography-tandem mass spectrometry. EDCs were log-transformed and rescaled by their deviations (SD) when modeled relative to neonatal endpoints using linear regression adjusting for age, education, pre-pregnancy body mass index (BMI), serum cotinine, serum lipids for lipophilic chemicals, and a race/ethnicity interaction term; p-values had false discovery rate correction (<0.05). Results: The cohort comprised women aged 28 (SD = 5) years with normal BMIs (23.6 kg/m 2, SD = 3). Maternal EDC concentrations varied by self-identified race/ethnicity and neonatal outcomes, though no specific EDC was consistently associated with neonatal anthropometric outcomes across racial/ethnic groups. For the overall cohort, perfluorooctanoic acid was negatively associated with birth length per SD increase in concentration (β = −0.23 cm; 95% CI −0.35, −0.10), while perfluorohexanesulfonic acid was negatively associated with umbilical circumference (β = −0.26 cm; 95% CI −0.40, −0.13), perfluorodecanoic acid with arm length (−0.09 cm; 95% CI −0.14, −0.04), and PCBs congeners 118/106 (−0.12 cm; 95% CI −0.20, −0.04) and 146/161 (−0.14 cm; 95% CI −0.23, −0.05) with thigh length, as were 7 other poly-and-perfluorinated alkyl substances (PFASs). Conclusions: Among healthy pregnant women with low risk antenatal profiles and relatively low EDC concentrations, reductions in umbilical circumference and bone lengths may be a sensitive marker of intrauterine EDC exposure, particularly for PFAS. Highlights: 76 endocrine disruptor chemicals (EDCs) were measured in cohort of pregnant women. Newborns underwent standardized neonatal assessments at ≈1–2 days after birth. EDC were not associated with gestation, birth weight or head circumference. Reductions in umbilical circumference, birth length, arm and thigh length were found. Poly-and-perfluorinated alkyl substances were most often associated with reductions.